2019
DOI: 10.1088/1757-899x/673/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of Ag doped ZnO particles via flame pyrolysis method for degradation of methylene blue

Abstract: Flame pyrolysis is widely used for the fabrication of particles because of great crystallinity and fine size distribution of the products. In this research, ZnO-Ag particle materials have been favourably made by flame pyrolysis. The impacts of Ag loading varying from 0 to 20 wt% on the photocatalytic activity of ZnO-Ag particle under ultraviolet (UV) and sunlight irradiations were studied. ZnO-Ag particles were fabricated based on zinc acetate dihydrate (Zn(CH3COO)2.2H2O) 0.1 M and silver nitrate (AgNO3) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…When the XRD image was adjusted by JCPDS (Joint Committee on Powder Diffraction Standards), the ZnO particles obtained were in the form of hexagonal wurtzite (w-ZnO) [20]. Where in a previous study (Wang et al, 2012) it was stated that w-ZnO is the most stable structure and is most often found at ambient or normal pressure and a stable thermodynamic phase [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the XRD image was adjusted by JCPDS (Joint Committee on Powder Diffraction Standards), the ZnO particles obtained were in the form of hexagonal wurtzite (w-ZnO) [20]. Where in a previous study (Wang et al, 2012) it was stated that w-ZnO is the most stable structure and is most often found at ambient or normal pressure and a stable thermodynamic phase [14].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the product has high crystallinity and narrow size distribution. Product properties, such as: crystal size, crystal phase, degree of aggregation and agglomeration, surface area, and porosity can also be controlled by adjusting the flame conditions [14]. To the best of our knowledge, the effect of the flowrate on the flame process on the formation of ZnO-Ag composite materials has not been explored.…”
Section: Introductionmentioning
confidence: 99%